40 years old LNG stainless steel pipeline: Characterization and mechanical behaviour. (September 2017) - Sanchez, Javier; Galao, Oscar; Torres, Julio; Fullea, Jose; Andrade, Carmen; Garcia, Julio C.; Ruesga, Javier; Cano, Pedro
Abstract: Stainless steel is a corrosion resistant metal that has now wide record of good performance in several aggressive media, in spite of which is not fully immune to different types of attack. In present work is presented the performance of 304 stainless steel as forming part of the tubes of a tank that has been operating from 1964 for Liquefied Natural Gas storage. The stainless steel tubes are part of a pipeline connecting the Liquefied Natural Gas tanks TK-1200A/B at the Barcelona plant. The pipeline had been continuously operating for more than 40 years, with cooling cycles from ambient temperature down to cryogenic temperatures. The paper shows that the working conditions and the marine environment did not embrittle or modify the properties of the tubes. Highlights: Austenitic stainless steel resists the GNL and environmental conditions. Temperature fluctuations and marine environment do not embrittle the steel. Welds present no damage. Base material and welds keeping high ductility behaviour. Base material and welds keeping high tolerance of damage.